The Relevance of Law Number 28 of 2004 concerning Foundations in the Development of Educational and Social Institutions in Indonesia - Aji, Ahmad Mukri; Yunus, Nur Rohim; Mukri, Syarifah Gustiawati (SALAM: Jurnal Sosial dan Budaya Syar-i, 2024)
Foundations have a strategic role in organising educational services and social activities in Indonesia. As a non-profit entity, foundations are expected to contribute to community development through professional and sustainable management of academic and social institutions. However, in practice, there are still many deviations in the management of foundations, especially related to governance, financial transparency, and asset protection. This study aims to analyse the relevance of Law Number 28 of 2004 concerning Foundations in supporting the development of educational and social institutions in Indonesia, with a focus on legal provisions, implementation in the field, and implementation challenges. This study uses a qualitative method with a legislative and conceptual approach. Data were collected through document studies of laws and regulations, scientific journals, and case studies of relevant educational and social foundations. The analysis was carried out descriptively-analystically to identify the effectiveness of the regulation and its suitability to the community's actual needs. The study results indicate that Law No. 28 of 2004 has provided a relatively solid legal framework in regulating the organisational structure of foundations, non-profit principles, and restrictions on conflicts of interest. However, there are still weaknesses in the implementation aspect, such as the lack of understanding of foundation administrators regarding legal obligations and weak oversight mechanisms. Therefore, it is necessary to revise several legal norms to be more responsive to educational and social needs, improve legal education for foundation managers, and strengthen the role of guidance by the Ministry of Law and Human Rights.Keywords: Foundation; Law No. 28 of 2004; education; social activities; governance.